Proposed business model strategy for PT. Bintoro Bangun Indonesia in contractor business - Mia Virgiyanthi; Wawan Dhewanto (LPPM STIE Krakatau, 2025)
Purpose: This study aims to design a business model strategy to address PT. Bintoro Bangun Indonesia’s challenge in increasing sales and scaling up its contractor business, aligning with market opportunities and company vision. Methodology/approach: A qualitative case study was conducted using interviews, observations, and company documents, analyzed with the Business Model Canvas (BMC) and SWOT. Results/findings: The study proposes a New BMC with innovations in all nine building blocks, adding a home-buyer segment, housing development, property sales, expanded channels, and aligned resources, activities, partnerships, and costs to support growth. Conclusions: The proposed model integrates existing contractor services with housing development, enabling scalability, synergy, and competitive advantage in the dynamic Indonesian market. Limitations: Findings are limited to a single company context and qualitative scope, with external macroeconomic factors acknowledged but not modeled. Contribution: This study demonstrates practical use of the BMC for strategic transformation in the contractor sector, offering insights for diversification and sustainable growth.